New insights in neutrophil extracellular traps: Its possible association in COVID-19 pathogenesis - Komal Fanda; Pallavi Sharma; Vikas Jindal; Ranjan Malhotra; Amit Goel; Malvika Thakur; Shivali Vashisht (Wolters Kluwer Medknow Publications, 2020)
Neutrophils discovered by Elie Metchnikoff are granulocytes that play a critical role as a first-line defense in innate immunity. They freely circulate in the blood vessels. Upon receiving the chemotactic gradient signal, neutrophils become the first white blood cells that get activated in various inflammatory sites, defending the human body from the microbial attack. The process of neutrophil extracellular traps (NETs) formation, through the neutrophil action mechanism, is a specific type of cell death, known as NETosis, distinct from necrosis and apoptosis. Oxidative burst mechanisms kill the pathogens trapped in NETs by two procedures - production of reactive oxygen species and chromatin unfolding. The mechanism of NETs draws an analog with the pathogenesis of periodontitis due to dysregulated neutrophilic response to specific bacterial species found in subgingival plaque. NETs are a fibrous structure that consists of a backbone of chromatin with attached globular domains. There are granular proteins and peptides in these domains as well as some cytoplasmic components. The core histones-A potent antimicrobials (H2A, H2B, H3, and H4) that together account for around 70% of the protein mass are the key component of the system. In this NETs-novel coronavirus disease-19 (nCOVID-19) intriguing centric overview, we have a mechanism for NET production; the ability of NETs to entrap and kill pathogens, including the potential immunogenicity of NETs in disease. We have also speculated a few comments on the possible role of NETs in the nCOVID-19.